Google Form Training for Healthcare Professionals to Enhance Services at Belimbing Health Center, Padang City - Yuli Mardi; Syamsul Kamal; Vanya Putri Ramadhani (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Google Form is one of Google's free applications that serves various purposes. This application assists in managing registrations, creating opinion surveys, gathering social data, crafting short quizzes, and performing various other functions. Google Form also enables users to create and analyze surveys directly through a web browser. Another advantage is its capability for collaborative work with multiple individuals simultaneously, and all changes are automatically saved. To enhance services in healthcare facilities, medical professionals and healthcare staff can utilize Google Form to create health service surveys, record data for patients requiring special care, monitor infants at community health posts, and similar activities. However, many medical professionals and healthcare staff at Belimbing Health Center are not yet familiar with the free and instant Google Form application provided by Google. Hence, a socialization activity on the use of Google Form is needed for them. The purpose of this activity is to provide training to medical professionals and healthcare staff at Belimbing Health Center to enable them to effectively utilize Google Form, thus enhancing their performance in patient care at the health center. This Google Form usage training was conducted as a form of community service at Belimbing Health Center, Padang City, on September 23, 2023. The training began with the delivery of Google Form materials, followed by practical exercises in creating Google Forms. The expected outcome of this activity is that medical professionals and healthcare staff can use Google Form effectively and implement it according to their needs to support their work seamlessly.